Clinicopathological profile of patients with brain secondaries from Ca cervix: a case series of five patients from tertiary cancer centre in North India - Sharma, Jyoti; Upadhyay, Mrinalini; Gupta, Manish; Fotedar, Vikas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Ca cervix is a common gynaecological cancer in daily practice but secondaries in brain after ca cervix as primary is a rare occurrence. As the survival of ca cervix patients has improved, we are able to encounter secondaries in unusual sites like brain. Prognosis is usually dismal due to presence of extra cranial mets along with brain secondaries which limits the use of new radiotherapy techniques like Stereotactic radiosurgery. We present a case series of five patients who presented to us post radical treatment of cancer cervix and treated with whole brain radiation therapy and best supportive care.